Tiknūlūjiyā al-Taʿlīm al-Muqtaraḥah li-Taʿlīm Mahārat al-Kalām li-Ṭullāb al-Mustawā al-Mutawassiṭ fī Indūnīsiyā - Abdul Hafidz Zaid (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2014)
Scholars have emphasized that speaking skill is one of the primary objectives of foreign language instruction. This competence can only be developed through continuous practice and sustained communicative exercises. For this reason, educational institutions dedicated to foreign language teaching encourage their students to use the target language actively in their daily lives. To develop speaking proficiency among students at the intermediate level, close collaboration is required among all stakeholders, including teachers, curriculum developers, educational experts, and other relevant parties. Such cooperation is essential to achieve the desired learning outcomes and to ensure the effectiveness of language instruction. In this article, the author proposes several educational technologies and instructional strategies designed to enhance the speaking skills of intermediate-level students in Indonesia. These recommendations are intended to support more effective and engaging foreign language learning.